Skepticism as the Rudimentary Nature: A Postmodernist Approach to Muhammad Hafeez Khan’s Novel Adh Ahuray Lok: People with Lost Identities - Hussain, Mumtaz; Rind, Ume Kulsoom; Solangi, Suhail Ahmed; Ali, Faizan (Pakistan Journal of Humanities and Social Sciences, 2023)
This study examines the novel Adh Ahuray Lok (People with Lost Identities) by Muhammad Hafeez Khan from the perspective of skeptical nature in postmodernism. A significant amount of postmodernist theory relies on maintaining a skeptical attitude. The projects of philosophical postmodernism and philosophical skepticism appear deeply aligned, as both focus on doubting existing metanarratives and assumptions. They seek to justify the assumptions inherent in our systems of rationality, meaning, and truth. Furthermore, they challenge the modernist notion that objective knowledge is attainable or that we can confidently assert progress. The researcher has selected five diverse postmodernist theorists and incorporated one concept from each theorist to strengthen the argument regarding postmodernism's skeptical nature. The study employs a qualitative content analysis method to analyze the text of the chosen novel. The researcher concludes that postmodernism is rooted in skepticism, as supported by the analysis of the selected text.